Extraction, Modification and Biomedical Application of Agarose Hydrogels: A Review - Jiang, Feng; Xu, Xin-Wei; Chen, Fu-Quan; Weng, Hui-Fen; Chen, Jun; Ru, Yi; Xiao, Qiong; Xiao, An-Feng (Marine drugs, 2023)
Numerous compounds present in the ocean are contributing to the development of the biomedical field. Agarose, a polysaccharide derived from marine red algae, plays a vital role in biomedical applications because of its reversible temperature-sensitive gelling behavior, excellent mechanical properties, and high biological activity. Natural agarose hydrogel has a single structural composition that prevents it from adapting to complex biological environments. Therefore, agarose can be developed into different forms through physical, biological, and chemical modifications, enabling it to perform optimally in different environments. Agarose biomaterials are being increasingly used for isolation, purification, drug delivery, and tissue engineering, but most are still far from clinical approval. This review classifies and discusses the preparation, modification, and biomedical applications of agarose, focusing on its applications in isolation and purification, wound dressings, drug delivery, tissue engineering, and 3D printing. In addition, it attempts to address the opportunities and challenges associated with the future development of agarose-based biomaterials in the biomedical field. It should help to rationalize the selection of the most suitable functionalized agarose hydrogels for specific applications in the biomedical industry.